Peran Guru Pendidikan Agama Islam Dalam Meningkatkan Motivasi Belajar Siswa Difabel di SMA Negeri 1 Mojotengah Wonosobo - Aulya Nur Asmaul Husna; Hidayatu Munawaroh; Siti Lailiyah (Politeknik Kampar, 2024)
This research aims to: 1) determine the learning motivation of students with disabilities at SMA Negeri 1 Mojotengah; 2) to determine the role of Islamic religious education teachers in increasing the learning motivation of disabled students at SMA Negeri 1 Mojotengah; 3) to determine the obstacles for Islamic religious education teachers in increasing the learning motivation of disabled students at SMA Negeri 1 Mojotengah. This research uses a qualitative research approach with field research. Data collection techniques use observation, interviews and documentation methods. Then, data sources were obtained from primary data sources and secondary data sources (Islamic religious education books, references related to students with disabilities, learning motivation, previous theses, articles, journals and internet sites). Apart from that, data sources were also obtained from research subjects, namely the school principal, PAI subject teachers, and 5 students with disabilities at SMA Negeri 1 Mojotengah. The data analysis technique used is an inductive qualitative data analysis technique. Based on the research results, it can be concluded that the learning motivation of disabled students at SMA Negeri 1 Mojotengah is not good due to several factors, namely the less conducive learning environment, bullying, and the lack of self-confidence of disabled students. The role of PAI teachers in increasing learning motivation is as a demonstrator, class manager, facilitator and mediator, evaluator and motivator. Some of the obstacles for teachers in increasing the learning motivation of disabled students are in growing and increasing learning motivation because students lack self-confidence, inadequate facilities, communication with deaf disabled students, there is no special accompanying teacher (GPK) who accompanies them in class and integrates learning methods with needs of students with disabilities.